Prognostic role of early 18-FDG PET/CT during neoadjuvant chemotherapy for resectable adenocarcinoma of the esophagus and esophagogastric junction - Harustiak, Tomas; Zemanova, Milada; Fencl, Pavel; Pazdro, Alexandr; Snajdauf, Martin; Faltova, Hana; Lischke, Robert; Stolz, Alan Josef (Neoplasma, 2021)
We prospectively investigated whether metabolic response assessed by 18F-fluorodeoxyglucose positron emission tomography combined with computed tomography (PET/CT) early in the course of neoadjuvant chemotherapy is predictive of survival in patients with adenocarcinoma of the esophagus and esophagogastric junction. PET/CT was performed before and in the third week after the initiation of the first cycle of neoadjuvant chemotherapy, which consisted of epirubicin, cisplatin, and 5-fluorouracil or capecitabine. The metabolic response was defined as a relative decrease in the peak standardized uptake value (SUL) of the tumor by ≥35% or total lesion glycolysis (TLG) by ≥66%. The associations of metabolic response with overall survival (OS) and disease-free survival (DFS) were investigated using Kaplan-Meier curves and multivariable Cox regression analysis. Among 126 recruited patients, the early metabolic response was assessed in 107 patients (90 of them underwent surgical resection). The five-year OS and DFS rates of all patients were 28% and 27%, respectively. No difference was found in OS (p=0.10 for SUL, p=0.08 for TLG) or DFS (p=0.50 for SUL, p=0.20 for TLG) between metabolic responders and non-responders. Post hoc analysis of the patients with a follow-up PET/CT within 16 days showed that metabolic response reflected by SUL predicted OS (p=0.03). We concluded that metabolic response assessed by PET/CT after the first cycle of neoadjuvant chemotherapy does not predict survival in patients with adenocarcinoma of the esophagus and esophagogastric junction. However, proper timing of the follow-up PET/CT may affect the prognostic ability of the early metabolic response.
Keywords: prognóza; Prognosis; Radiopharmaceuticals; radiofarmaka; fluorodeoxyglukosa F18; Humans; Neoadjuvant Therapy; lidé; retrospektivní studie; Fluorodeoxyglucose F18; Adenocarcinoma; gastroezofageální junkce; PET/CT; Retrospective Studies; Esophagogastric Junction; Positron Emission Tomography Computed Tomography; adenokarcinom; neoadjuvantní terapie